(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2021)
The genetic contribution in stroke onset depends on the stroke subtypes. Understanding the genetic mechanism may influence the future direction in stroke management. There is complex interplay of genetic and environmental factors for any stroke event. Very small proportion of stroke is attributable to mendelian disorders. Stroke may also manifest as part of a syndromic disease in the form of single gene multisystem disorder. But there is no direct contribution of genetic polymorphism in conventional stroke subtypes. Specific genetic loci increase the suspectibility to development of hypertension, diabetes, dyslipideamia or influence the coagulation pathway or chance of atheroma formation and embolism. While chr9p21 locus or PITX2 and ZFHX3 are related to cardioemetabolic, HDAC9, TSPAN2 and 9p21 locus are responsible for the large vessel occlusion. On the otherhand, genome-wide significant locus on chromosome 1q22 the APOE locus are found to have significant association with intracerebral hemorrhage. But the direct pathophysiologic relationship of genetic plymorphirsm may be linked to onset of sub arachnoid hemorrhage. MMP-3, endothelial nitric oxide synthase (eNOS), tumor necrosis factor (TNF)-α, VCAM-1 etc have been found to be responsible for intracranial aneurysm formation, growth and risk of rupture. Journal of National Institute of Neurosciences Bangladesh, January 2021, Vol. 7, No. 1, pp. 75-86